2015
DOI: 10.1007/s10620-015-3547-6
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Intraluminal Radiofrequency Ablation for Malignant Extrahepatic Biliary Obstruction: A Safe and Feasible Method

Abstract: Percutaneous intraluminal RFA combined with biliary stenting is a safe and feasible therapeutic option for unresectable extrahepatic malignant biliary obstruction. Multiple central prospective controlled trials are necessary for the long-term benefits of RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 11 publications
3
15
1
1
Order By: Relevance
“…The 7-month stent patency reported here (95% CI: 5.3, 8.7) is in agreement with the results of the study reported by Werner et al (median metal stent patency: 7.3 months) [29] but is higher than that reported by Tian-Tian et al (stent patency: 5.0 months) [28]. Our study and that reported by Werner et al had higher rates of cholangiocarcinoma (50% and 88%, respectively) and sequential chemotherapy (14% and 41%, respectively) compared with the rates in the trial reported by Tian-Tian et al (48% and 4%, respectively), which is a possible explanation for this discrepancy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The 7-month stent patency reported here (95% CI: 5.3, 8.7) is in agreement with the results of the study reported by Werner et al (median metal stent patency: 7.3 months) [29] but is higher than that reported by Tian-Tian et al (stent patency: 5.0 months) [28]. Our study and that reported by Werner et al had higher rates of cholangiocarcinoma (50% and 88%, respectively) and sequential chemotherapy (14% and 41%, respectively) compared with the rates in the trial reported by Tian-Tian et al (48% and 4%, respectively), which is a possible explanation for this discrepancy.…”
Section: Discussionsupporting
confidence: 92%
“…The potential therapeutic effect of combined RFA and stent placement has only been evaluated in a few studies to date, with mixed findings reported [9, 19, 20, 28, 29]. The 7-month stent patency reported here (95% CI: 5.3, 8.7) is in agreement with the results of the study reported by Werner et al (median metal stent patency: 7.3 months) [29] but is higher than that reported by Tian-Tian et al (stent patency: 5.0 months) [28].…”
Section: Discussionmentioning
confidence: 99%
“…41 To date, numerous additional case series have evaluated the use of endoscopic biliary RFA for the treatment of malignant biliary strictures. 33,[42][43][44][45][46][47][48][49][50][51][52] Of these included studies, Figueroa-Barojas et al 47 showed encouraging clinical data reporting pre-and post-RFA luminal diameter of the stricture to have significant improvement (1.7 mm; range, 0.5-3.4 vs 5.2 mm; range, 2.6-9, respectively). Additional studies have described similarly impressive results, with 1 study reporting a pooled mean increase in stricture diameter of 3.7 mm after RFA therapy.…”
Section: Malignant Biliary Stricturesmentioning
confidence: 99%
“…У одного больного отмечено развитие внутрибрюшного кровотечения, не потребовавшего оперативного пособия. Средняя проходимость установленных стентов составила 149 дней (5 мес), медиана общей выживаемости пациентов -181 день (6 мес) с момента выполнения первой РЧА у каждого пациента [11].…”
Section: радиочастотная абляцияunclassified